Report on practical training at Perpustakaan Sulatanah Zanariah, Universiti Teknologi Malaysia, Skudai - Nurunadiah Baharum, author; Fakulti Sains (Kedah : Universiyti Teknologi Mara (UiTM), 2009)
Sarjana (Library and Information Management)) - Universiyti Teknologi Mara (UiTM),2009